Consumption of Cariogenic Food and Nutritional Status of Children in PAUD Ummu Aiman Kartasura Sukoharjo - Nurul afifa; Muwakhidah Muwakhidah (Journal of Nutraceuticals and Herbal Medicine, 2020)
The state of infection and food intake is a direct factor affecting nutritional status. The frequency of children consuming cariogenic foods that generally contain many carbohydrates can certainly affect the child's nutritional intake. If it happens for a long time and is not offset by variations of nutritious food, then the child will deficiency other macronutrients and micronutrients. Based on a preliminary survey conducted in PAUD UMMU AIMAN Kartasura Sukoharjo, known 3% of children had more nutrition, 10% had undernutrition, and 87% were normal. The objective of this was study to know the relationship between cariogenic food consumption with nutritional status in children aged 3-5 years in PAUD UMMU AIMAN Kartasura Sukoharjo. The method of this study was an observational study with a cross-sectional study design. The frequency data of cariogenic food consumption was obtained by using a food frequency (FFQ), nutritional status data was obtained by using direct measurement of height and weight of the student. Data were analyzed using Fisher's Exact Test. The result was 52.8% of respondents had low cariogenic food consumption levels, and 47.2% had high levels of dietary cariogenic consumption. That as many as 13.9% of respondents have abnormal nutritional status, while 86.1% have normal nutritional status. There was a correlation between consumption of cariogenic food and nutritional status (p = 0.016).